Attorney General John Van de Kamp Keynotes Fresno County Bar Association Law Day Luncheon - Watkins, Howard::::::::: (1983)
John McGregor and Howard Watkins holding John's Fresno County-Voluntary Legal Services' Pro Bono of the Year Award John handled the first FC-Voluntary Legal Services Program case to go to trial